2010
DOI: 10.1186/1755-1536-3-16
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of pirfenidone and its novel targets

Abstract: Background Pirfenidone (PFD) is a molecule that exhibits antifibrotic properties in a variety of in vitro and animal models of lung, liver and renal fibrosis. These pathologies share many fibrogenic pathways with an abnormal fibrous wound-healing process; consequently, tissue repair and tissue regeneration-regulating mechanisms are altered. Objective To investigate the usefulness of PFD as an antifibrotic agent in clinical and experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 62 publications
8
95
0
1
Order By: Relevance
“…Earlier studies describing TGF-β blockade by PFD, inhibiting fibroblast-to-myofibroblast differentiation, may support this suggestion. [30][31][32] The positive effects of PFD on the scarred LP reflect effective delivery, a long duration of action, and drug migration into tissue layers between the LP and muscle, as demonstrated (using ink) in our previous article. 17 The localization of PFD to, and drug duration in, the targeted layer (that between the deep LP and muscle adjunct to scar tissue) are critical.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies describing TGF-β blockade by PFD, inhibiting fibroblast-to-myofibroblast differentiation, may support this suggestion. [30][31][32] The positive effects of PFD on the scarred LP reflect effective delivery, a long duration of action, and drug migration into tissue layers between the LP and muscle, as demonstrated (using ink) in our previous article. 17 The localization of PFD to, and drug duration in, the targeted layer (that between the deep LP and muscle adjunct to scar tissue) are critical.…”
Section: Discussionmentioning
confidence: 99%
“…The antifibrotic action of PFD has also been reported in several animal models of progressive fibrotic disorders of other organs, including the kidney, liver, and heart. 14,15 Thus, one advantage for applying PFD as an new antifibrotic medicine for VF scars is that PFD has already been approved for clinical use in progressive fibrotic disorders of other organs.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b1 is one of the most studied profibrotic cytokines. 14,15 In the lung, TGF-b1 is produced by a wide variety of cell types, including alveolar macrophages, neutrophils, activated alveolar epithelial cells, endothelial cells, fibroblasts, and myofibroblasts. TGF-b1 induces the proliferation of macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…117 Pirfenidone, that is, pyridine(5-methyl-1-phenyl-2-(1H)-pyridone), is an oral agent that can elicit antiinflammatory, antioxidative, and antiproliferative effects. 118 Even though, the exact mechanism of action is still not fully understood, the antifibrotic effect of pirfenidone has been demonstrated in several organs, for example lung, liver, and kidney. 118 In human liver cells, it has been shown that it attenuates TGF-β-induced mRNA expression of α-SMA and type I collagen.…”
mentioning
confidence: 99%